The Ethical Principles Governing the Engineering of the Islamic Financial System - Sayyed taleb Alavi (اخلاق وحیانی, 2013)
Unlike the common financial systems, the Islamic financial system is ethics-centered. Therefore, the engineering of the Islamic financial system must be organized based on moral principles and norms. These principles and norms which have been specified in the original Islamic references such as the Quran and the tradition, determine the rights and duties of the participants in an Islamic financial system, and clarify the rights of the units with surplus resources (i.e. the savers) and the units with shortage of resources (i.e. the investors). In any case, and by referring to the Quran and the traditions, it is possible to identify some of the governing principles and ethical norms in this regard, such as making sure the money is not usurious,that a transaction is not aleatory (extremely uncertain),and that there is no gambling involved (illegitimate windfall), as well as identifying deficiencies such as the absence of price control, market manipulation and interference, and factors such as transaction fees at fair prices, the right to access accurate, sufficient and equal information, and the absence of any loss, extreme lesion, ignorance, hording, … etc.